In Vitro Antifungal Activity and Chemical Composition of Piper auritum Kunth Essential Oil against Fusarium oxysporum and Fusarium equiseti - César Chacón; Emanuel Bojórquez-Quintal; Goretty Caamal-Chan; Víctor M. Ruíz-Valdiviezo; Joaquín A. Montes-Molina; Eduardo R. Garrido-Ramírez; Luis M. Rojas-Abarca; Nancy Ruiz-Lau (Agronomy, 2021)
The essential oils of plants of the genus Piper have secondary metabolites that have antimicrobial activity related to their chemical composition. The objective of our work was to determine the chemical composition and evaluate the antifungal activity of the aerial part essential oil of P. auritum obtained by hydrodistillation on Fusarium oxysporum and Fusarium equiseti isolated from Capsicum chinense. The antifungal activity was evaluated by direct contact and poisoned food tests, and the minimum inhibitory concentration (MIC50) and maximum radial growth inhibition (MGI) were determined. The identification of oil metabolites was carried out by direct analysis in real time mass spectrometry (DART-MS). By direct contact, the essential oil reached an inhibition of over 40% on Fusarium spp. The 8.4 mg/mL concentration showed the highest inhibition on F. oxysporum (40–60%) and F. equiseti (>50%). The MIC50 was 6 mg/mL for F. oxysporum FCHA-T7 and 9 mg/mL for F. oxysporum FCHJ-T6 and F. equiseti FCHE-T8. DART-MS chemical analysis of the essential oil showed [2M-H]− and [M-H]− adducts of high relative intensity that were mainly attributed to eugenol and thymol/p-cimen-8-ol. The findings found in this study show a fungistatic effect of the essential oil of P. auritum on Fusarium spp.